(untitled) (Práxis Educativa, 2023)
The aim of the research was to investigate the establishing process of the Institutional Policy (IP) of teacher education at the Federal University of Rio Grande (FURG) accordingly the Nacional Curriculum Guidelines issued by Resolution CNE/CP no. 2/2015. It was a qualitative documental investigation, supported by semi-structured interviews with key subjects in the actuation process of the policy. Based on the Theory of policy enactment of Ball, Maguire and Braun (2016), the enactment process of these guidelines in the context of practice was investigated, through documents, texts, artefacts and discourses of key-subjects, in order to map the interpretation and translation movement of this policy, which resulted on the approved IP on teacher education at that university. Keywords: Teacher education. Policy enactment. Institutional Policy.